Effects of heart disease on the growth and development of Filipino children ages 0-6 years - Decena, Aurora Zerrudo
The study sought to investigate the effects of heart disease on the growth and development of Filipino children ages 0-6 years. The following hypotheses were posed: 1. Children ages 0-6 years with heart disease will exhibit significant delays in growth. 2. Children with heart disease will exhibit significant delays in the physical, motor and personal-social areas of development more than the language-cognitive area. 3. Children with congenital heart disease will show significantly greater delays in growth and development than children with acquired heart disease. 4. Children with congenital cyanotic heart disease will show significantly greater delays in growth and development than children with congenital acynotic heart disease. 5. Children with multiple anomalies/pathologies in addition to heart disease will show significantly greater delays in growth and development than children with puse heart disease. 6. Children with heart disease who have frequent bouts of infection will show significantly greater delays in growth and development than those who have infrequent bouts of infection. 7. Children with heart disease who belong to the low socio-economic group will exhibit significantly greater delays in growth and development than children with heart disease who belong to the upper-middle socio-economic levels. 8. Male children with heart disease will show significantly greater delays in growth and development than female children. 200 Filipino children with heart disease, 103 boys and 97 girls with ages ranging from 18 days to 6 years, 5 months, 7 days, seen and examined at the out-patient and in-patient departments of the Philippine General Hospital (PGH) and the Philippine Heart Center for Asia (PHCA) from July 12, 1977 to September 30, 1977 were taken as subjects. On growth. Overall height and weight findings were analyzed using the T-test based on the Philippine norms developed by the Food and Nutrition Research Center (FNRC). Comparative height-weight findings for each of the study groups were subjected to covariance analysis and F-test for significance. On development. Median values were obtained by Logit analysis which were then subjected to computation for statistical significance. Cochran's test was utilized to compare total number of delays for each of the 4 sectors of development. The following results obtained on development: 1. 2 variables, namely, (1) kind of heart disease and (2) respiratory infections were significantly associated with the personal-social development of the children under study. 2. Only 1 variable, kind of heart disease, was significantly associated with the fine motor-adaptive development of the children under study. 3. 3 variables, namely, (1) type of heart disease, (2) kind of heart disease and (3) respiratory tract infections were significantly associated with the language development of the children under study. 4. 3 variables, namely, (1) type of heart disease, (2) kind of heart disease, and (3) sex, were significantly associated with the gross motor development of the children under study. 5. The variable, socio-economic status, did not show any significant finding on all 4 sectors of the Denver Development Screening Test. Recommendations: 1. That further study be conducted with a larger number of subjects. 2. That the study results on the development parameter be re-examined in the light of Philippine norms on the Denver Developmental Screening Test, which will soon be developed. 3. That a follow-up study be done on the growth and development of these children as they grow older i.e. the school age and adolescent periods, to confirm the findings obtained in this study.